2007
DOI: 10.1177/1082013207085686
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Sorghum (Sorghum vulgare) and Corn Supplemented with Methionine on Cut-Up Pieces Weights of Broiler Carcass and Quality Properties of Breast and Drumsticks Meat

Abstract: This research was carried out to determine the effects of sorghum (BS ¼ basal diets containing 30% sorghum), corn (BC ¼ basal diets containing corn) and supplemental methionine (BSM ¼ diet BS plus 0.69% methionine, BCM ¼ diet BC plus 0.69% methionine) in broiler diets on the cold carcass weight and cut-up pieces weight of broilers and some chemical, physical and microbiological properties of breast and drumstick meats. A total 240 male (120) or female (120) broiler chicks (Ross-308) were allocated to four diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
11
2
Order By: Relevance
“…Besides the positive e ect of Met on the growth and feed conversion rate of the animals, Met supplementation is known to increase the breast and leg meat yield of broilers, irrespective of the Met source used [16][17][18][19][20]. Additionally, the abdominal fat content is reduced [3,11,18] as well as the absolute fat content in the llet [21]. e in uence of Met supplementation on lipogenesis is discussed as a potential support to producing lean poultry meat [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the positive e ect of Met on the growth and feed conversion rate of the animals, Met supplementation is known to increase the breast and leg meat yield of broilers, irrespective of the Met source used [16][17][18][19][20]. Additionally, the abdominal fat content is reduced [3,11,18] as well as the absolute fat content in the llet [21]. e in uence of Met supplementation on lipogenesis is discussed as a potential support to producing lean poultry meat [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, it was shown that Met supplementation has the ability to in uence important quality parameters of the meat. Increasing Met concentrations in the diet elevates the pH of broiler meat [21,24]. e meat color is affected by lowering the L * and b * value [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding sorghum to broilers improves carcass traits (Aksu et al . ) and some measures of the storage stability of broiler meat (Du et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Saponins and phenolic compounds found in the structure of Yucca schidigera (resveratrol, yuccaols A, B, C, D, E and yucaone A) have been shown to affect antioxidant activity positively owing to their redox property (Cheeke, 2009;Enginar et al, 2006). Aksu et al (2007) reported that the phenolic compounds found in sorghum significantly reduce lipid oxidation and thereby, positively affect meat quality. Nasri et al (2012) determined that the supplementation of lamb rations with Quillaja saponaria had no effect on lipid oxidation in the longissimus dorsi muscle.…”
Section: Discussionmentioning
confidence: 99%